P204 The impact of alternative (non-canonical) NF-κB pathway inhibition in preventing intestinal barrier dysfunction in IBD. (19th June 2022) - Tang, Joseph; Papoutsopoulou, Stamatia; Mackay, Simon; Paul, Andrew; Duckworth, Carrie; Pritchard, Mark
Abstract : Introduction: The pathogenesis of Inflammatory bowel disease (IBD) involves a complex interplay between genetic predisposition, environmental triggers, the immune system and gut microbiota. Failure of the intestinal barrier results in the invasion of microbes at the site of injury thus triggering an immune-mediated inflammatory response. Previously, we showed that Nfκb2 -/- mice with defects in the alternative NF-κB activation pathway were protected against lipopolysaccharide induced and dextran sulphate sodium induced epithelial injury compared to wild-type (WT) mice. Here we investigated the effect of inhibiting IKKα and NIK, both critical components of this pathway, in preventing epithelial injury using murine intestinal organoids (enteroids). Methods: Enteroids originated from C57BL/6J WT mice were cultured in 3D using Matrigel. On day 3 after passage, WT enteroids were either left untreated or pre-treated with 0.6μM of a proprietary IKKα inhibitor (IKKα-SMI) or 2μM of the NIK small molecule inhibitor (NIKSMI-1) for 24 hours. Enteroids in the treatment groups were then stimulated with either 30ng/ml TNF or 100ng/ml of Lymphotoxin-α1β2 (LT). The impact of IKKα and NIK inhibition was determined morphologically using the enteroid circularity score and by immunohistochemistry for active caspase-3 (apoptosis) and Ki-67 (proliferation). The expression of selected inflammation-related genes in enteroids at 24 and 48 hours after treatment was also evaluated using RT-qPCR. Results: Pre -treatment with either IKKα-SMI or NIKSMI-1 prevented LT-induced enteroid rounding. IKKα-SMI also attenuated TNF-induced enteroid rounding with a reduced abundance in active caspase-3 positive apoptotic cells at 48 hours compared to the TNF-only group. No differences in apoptosis or proliferation were found in the LT-treated groups. At the 48-hour timepoint, the expressions of Nfκb2, Tnf, Cxcl9 and Icam-1 were significantly increased compared to the TNF-naïve group, however there was no significant difference between the inhibitor+TNF and TNF only groups. Conclusions: TNF-induced enteroid rounding promoted the expressions of several inflammation related genes involved in NF-κB signalling pathways. Pharmacological inhibition of IKKα ameliorated both TNF-induced and LT-induced enteroid rounding with a significant decrease in TNF-induced apoptosis on histology. Together, these findings suggest that IKKα may be a potential novel therapeutic target for the prevention of inflammation in IBD.